Descriptive Study Of The Incidence Of Preeclampsy In Pregnant Women At Ajibarang II Health Center - Elisa Ulfiana; Khobibah Khobibah; Ida Farida (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2023)
Preeclampsia is a specific condition in pregnancy characterized by placental dysfunction and a maternal response to systemic inflammation with endothelial activation and coagulation (POGI, 2016). Preeclampsia is called a